The Effect of Project-Based Learning Method on Economics Learning Outcomes of Grade XI Students at State Senior High School 11 Jambi City - Gusti Ayu Pratiwi; Arpizal Arpizal; Novia Sri Dwijayanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examined the effect of the Project-Based Learning (PjBL) method on students’ learning outcomes in Economics. The research was motivated by low student participation and learning outcomes associated with the use of teacher-centered instructional methods. The study aimed to determine whether implementing PjBL significantly affected the learning outcomes of eleventh-grade students at State Senior High School 11 Jambi City. A quantitative approach with a quasi-experimental design using a nonequivalent control group design was employed. The sample consisted of two classes: XI F7 as the experimental group and XI F3 as the control group, with 36 students in each class. Data were collected through pre-test and post-test instruments and analyzed using descriptive statistics and hypothesis testing. The results showed that the mean score of the experimental group increased from 57.50 on the pre-test to 77.92 on the post-test, while the control group improved from 56.81 to 67.78. These findings indicate that the implementation of Project-Based Learning resulted in greater improvement in students’ learning outcomes than conventional teaching methods. Therefore, Project-Based Learning can be considered an effective instructional approach for improving students’ achievement in Economics.